The stories we carry [large type] - Pearson, Robin W. (Center Point Large Print, 2026)
"Glory Pryor has carved out a life for herself in Gilmore, North Carolina, cultivating a community around her bookstore, By the Book. While her business is a success, she carries the weight of stories of her own she's never told anyone. Glory's husband Eli thinks she has her arms wrapped too tightly around the could-have-beens, and that it's time for them to let go of the store as they head into their retirement years. Glory has different opinions on that--she's not ready to give up the dream she's built just yet. Then Adelle Simonette shows up with her young son, Bennett, and Glory's carefully controlled life begins to crumble. Newly widowed Adelle is a single mother trying to find her footing and navigate parenting her young son. Lost in her grief, one thing she's certain of is that she needs to confront Glory Pryor and everybody who knows her because the woman's been living a lie. Adelle thinks it's high time Glory made things right. But Adelle's finding it hard to tell the truth . . . and there will be no going back once she does. In the wake of deeply personal grief and loss, two women reckon with a lifetime of silence and secrets to find a path forward toward healing, hope, and restoration."--